2014
DOI: 10.1016/j.devcel.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

ICR Noncoding RNA Expression Controls Imprinting and DNA Replication at the Dlk1-Dio3 Domain

Abstract: Imprinted genes play essential roles in development, and their allelic expression is mediated by imprinting control regions (ICRs). The Dlk1-Dio3 locus is among the few imprinted domains controlled by a paternally methylated ICR. The unmethylated maternal copy activates imprinted expression early in development through an unknown mechanism. We find that in mouse embryonic stem cells (ESCs) and in blastocysts, this function is linked to maternal, bidirectional expression of noncoding RNAs (ncRNAs) from the ICR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 64 publications
12
81
0
Order By: Relevance
“…The open chromatin signature of the corresponding region on the maternal allele of the IG-DMR could enable an activating function of AFF3 through this enhancer for regulating expression of the Dlk1-Dio3 locus, which is transcribed as a single polycistron. Consistent with these findings, a recent study found that enhancer-like noncoding RNAs emanating from the Dlk1-Dio3 ICR were required for the expression of the maternally expressed genes in the cluster (Kota et al 2014).…”
Section: Meg3 Mirnas Rian Mirnas Mirg Mir882supporting
confidence: 67%
“…The open chromatin signature of the corresponding region on the maternal allele of the IG-DMR could enable an activating function of AFF3 through this enhancer for regulating expression of the Dlk1-Dio3 locus, which is transcribed as a single polycistron. Consistent with these findings, a recent study found that enhancer-like noncoding RNAs emanating from the Dlk1-Dio3 ICR were required for the expression of the maternally expressed genes in the cluster (Kota et al 2014).…”
Section: Meg3 Mirnas Rian Mirnas Mirg Mir882supporting
confidence: 67%
“…In agreement with low levels of Dlk1 transcription in pluripotent cells (Kota et al, 2014), no reporter gene expression could be detected in naïve iPSCs. However, exposure to the differentiation-inducing agent retinoic acid (RA) yielded cells with readily detectable reporter gene fluorescence.…”
Section: Resultsmentioning
confidence: 54%
“…In some contexts, nuclear lamina association has previously been shown to lead to reduction in gene expression (Finlan et al 2008). It has recently been shown that in ES cells, the maternally inherited Dlk1-Dio3 chromosome, which is highly expressed for Meg3 (Gtl2), is preferentially located internally in the nucleus, and the paternally inherited locus from which little expression is observed is located peripherally (Kota et al 2014). Perturbation of maternal gene expression by knocking down expression from the IG-DMR resulted in more peripheral localization, indicating that lack of expression itself may target a region to the periphery (Kota et al 2014).…”
Section: Gain Of Function In Gene Regulation and Chromosome Architecturementioning
confidence: 99%
“…It has recently been shown that in ES cells, the maternally inherited Dlk1-Dio3 chromosome, which is highly expressed for Meg3 (Gtl2), is preferentially located internally in the nucleus, and the paternally inherited locus from which little expression is observed is located peripherally (Kota et al 2014). Perturbation of maternal gene expression by knocking down expression from the IG-DMR resulted in more peripheral localization, indicating that lack of expression itself may target a region to the periphery (Kota et al 2014). Here, we show that upon maternal transmission of del L1rep , no significant changes in Meg3 (Gtl2) expression or any other genes in the domain was observed in any tissues analyzed.…”
Section: Gain Of Function In Gene Regulation and Chromosome Architecturementioning
confidence: 99%